Invasively Measured Aortic Systolic Blood Pressure and Office Systolic Blood Pressure in Cardiovascular Risk Assessment in CKD - Christian D. Peters; Kevin K.W. Olesen; Esben Laugesen; Michael Mæng; Hans Erik Bøtker; Per L. Poulsen; Niels Henrik Buus (Kidney International Reports)
Introduction: Central aortic blood pressure (BP) could be a better risk predictor than brachial BP. This study examined whether invasively measured aortic systolic BP improved outcome prediction beyond risk prediction by conventional cuff-based office systolic BP in patients with and without chronic kidney disease (CKD). Methods: In a prospective, longitudinal cohort study, aortic and office systolic BPs were registered in patients undergoing elective coronary angiography (CAG). CKD was defined as estimated glomerular filtration rate (eGFR) <60 ml/min per 1.73 m2. Multivariable Cox models were used to determine the association with incident myocardial infarction (MI), stroke, and death. Results: Aortic and office systolic BPs were available in 39,866 patients (mean age: 64 years; 58% males; 64% with hypertension) out of which 6605 (17%) had CKD. During a median follow-up of 7.2 years (interquartile range: 4.6–10.1 years), 1367 strokes (CKD: 353), 1858 MIs (CKD: 446), and 7551 deaths (CKD: 2515) occurred. CKD increased the risk of stroke, MI, and death significantly. Office and aortic systolic BP were both associated with stroke in non-CKD patients (adjusted hazard ratios with 95% confidence interval per 10 mm Hg: 1.08 [1.05–1.12] and 1.06 [1.03–1.09], respectively) and with MI in patients with CKD (adjusted hazard ratios: 1.08 [1.03–1.13] and 1.08 [1.04–1.12], respectively). There was no significant difference between prediction of outcome with office or aortic systolic BP when adjusted models were compared with C-statistics. Conclusion: Regardless of CKD status, invasively measured central aortic systolic BP does not improve the ability to predict outcome compared with brachial office BP measurement.